Pentanacci and Pentanacci-Lucas hybrid numbers - Isbilir, Zehra; Gurses, Nurten (TARU PUBLICATIONS, 2023)
The aim of this study is to introduce the Pentanacci and Pentanacci-Lucas hybrid numbers. Then, some properties with respect to these special numbers and relations between them are obtained. In addition, matrix formulations, generating functions, Binetlike formulas and some summation formulas of them are examined.
Keywords: Pentanacci numbers; Pentanacci-Lucas numbers; Hybrid numbers; Pentanacci hybrid numbers; Pentanacci-Lucas hybrid numbers; MATRIX; Mathematics